Determinación serológica para las enfermedades de Newcastle y bronquitis infecciosa en las aves de combate de Bucaramanga - Diaz, Jorge; Rios, Helmunth; Moreno, Omar (Spei Domus, 2005)
Serological determination of Newcastle disease and Infectious Bronchitis antibodies in combat roosters in Bucaramanga city. The purpose of the present study was to detect Newcastle disease and Infectious Bronchitis antibodies in combat roosters in Bucaramanga city. Newcastle disease virus (NDV) is an avian paramixovirus – 1 containing a single strand negative sense RNA and coding for six proteins: Hemagglutinin, Neuraminidase, fusion protein, matrix protein, phosphoprotein and RNA dependet RNA polymerase. Newcastle disease clinical symptoms depending on virus strain. The main disease symptoms are respitory, diarrheic, circulatory disturbances and in chronic cases, impairment of the central nervous system. Infectious Bronchitis virus (IBV) belongs to the family coronaviridae contained three structural proteins: the “S” glycoprotein, located in the spike; the membrane “M” protein on the surface located and the “N” protein internally located. Infectious Bronchitis disease is considered one of the most important causes economical loss producing high mortality, reduced growth rates in chicks and oviduct lesions in laying hens impairing egg production. 140 combat animals were randomly selected, and sample from 22 property the Bucaramanga city; serum samples were rum using the Haemagglutination Inhibition test (HI) and the Indirect ELISA test for detection of antibodies to Newcastle disease and Infectious Bronchitis disease. Seroprevalence was calculated by dividing the number of positive sera by the total number of sample; seroprevalence was 36.4% for the Newcastle disease and 47.1% for the Infectious Bronchitis disease.